Notification Strategy and Predictors of Outcome in Stroke Ineligible for Reperfusion Therapies - Mirolovics, Ágnes; Bokor, Magdolna; Dobi, Balázs; Zsuga, Judit; Bereczki, Dániel (Frontiers in Neurology, 2019)
Background, objective: At least 70% of all stroke patients are ineligible for recanalization therapy. We identified predictors of outcome among these patients, with special focus on notification of emergency medical services (EMS). Methods: We prospectively collected data of 250 consecutive patients with acute cerebrovascular diseases ineligible for recanalization therapy. Initial notification strategy and outcome were analyzed by regression models. Results: EMS notification rate was 55%, 41% and 21% in patients with <6 hours, 6-24 hours and >24 hours stroke-to-door time. Atrial fibrillation (AF; OR=2.66, 95% CI:1.19-5.96), stroke severity (National Institutes of Health Stroke Scale score, NIHSS; OR=1.12, 95% CI:1.02-1.23), history of any psychiatric disease (OR=2.2, 95% CI:0.98-4.97), aphasia (OR=1.99, 95% CI:0.99-3.98) and residence type were predictors of EMS notification. Disability (modified Rankin Scale score [mRS]) both at discharge and at one year was associated with age, admission NIHSS score, type of cerebrovascular disorder, and prestroke mRS at discharge and discharge mRS at follow-up. Age (HR=1.05, 95% CI:1.02-1.08) and NIHSS (HR=1.16, 95% CI:1.12-1.21) had significant effect on the relative hazard of death. Conclusions: EMS notification is influenced by AF, stroke severity, psychiatric disease, aphasia and residence type. Early disability depends on age, the type and severity of the stroke and prestroke mRS. Predictors of disability at 1 year after stroke are age, stoke severity, mRS at discharge, and recurrent ischemic stroke. Higher NIHSS and older age are associated with higher case fatality. In patients ineligible for recanalization, EMS notification had no significant effect on outcome, regarding both disability and survival.